Cutting resistance of metal-ceramic interpenetrating composites. Issue 2 (1st February 2017) - Liu, Jing; Wu, Jinyu; Binner, Jon
Abstract: Metal-ceramic interpenetrating composites (IPCs) can be successfully manufactured by the pressureless infiltration of ceramic foams with molten metals. The resulting IPCs, in which both phases are three dimensionally continuous, have many potential applications, including wear and ballistic resistance amongst other uses. As these materials are extremely difficult to cut or machine, one potential application is for cut-resistant security materials. This project investigated their cutting resistance with a view to understanding the underpinning mechanisms. The composites were produced by infiltrating Al-10 wt% Mg alloy into gel-cast spinel and mullite foams of different densities at atmospheric pressure. Samples were subject to cutting using a diamond slitting wheel to determine cutting rates under different conditions and the cut products, cutting tools and debris were characterised, primarily using a range of electron microscopy-based techniques. As expected, the cutting resistance was found to be largely dependent on the hardness of the IPCs, however evidence was also found of the role that is played by the continuous metallic phase. Plastic deformation can consume energy and bridge cracks; strain hardening under the twin actions of compression and shearing can enhance the hardness and strength of the metal at the cut tips and adhesive wear is believed to be the main origin of rapid tool failure. In addition, metal-ceramic IPCs produced via pressureless infiltration show very good interfacial bonding between the phases.